2014
DOI: 10.3389/fneur.2014.00144
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatments Inhibiting Levodopa-Induced Dyskinesias in MPTP-Lesioned Monkeys: Brain Glutamate Biochemical Correlates

Abstract: Anti-glutamatergic drugs can relieve Parkinson’s disease (PD) symptoms and decrease l-3,4-dihydroxyphenylalanine (l-DOPA)-induced dyskinesias (LID). This review reports relevant studies investigating glutamate receptor subtypes in relation to motor complications in PD patients and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned monkeys. Antagonists of the ionotropic glutamate receptors, such as N-methyl-d-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…The only pharmacological treatment used to deal with L-DOPAinduced dyskinesia in PD patients is the noncompetitive antagonist of the N-methyl-D-aspartate (NMDA)-type glutamate receptor, amantadine (Blanpied, Clarke, & Johnson, 2005;Luginger, Wenning, B€ osch, & Poewe, 2000;Meissner et al, 2011;Metman et al, 1999;Ossola et al, 2011;Wandinger et al, 1999). Increased glutamatergic neurotransmission has been associated with the pathophysiology of L-DOPA-induced dyskinesia (Ahmed et al, 2011;Huot, Johnston, Koprich, Fox, & Brotchie, 2013;Morin & Di Paolo, 2014;Papa, Boldry, Engber, Kask, & Chase, 1995;Rylander et al, 2009;Solís, García-Sanz, Herranz, Asensio, & Moratalla, 2016). Nonetheless, pharmacotherapy with amantadine is limited due to the development of central adverse effects including dizziness, confusion, and hallucinations (Macchio, Ito, & Sahgal, 1993;Shannon, Goetz, Carroll, Tanner, & Klawans, 1987;Thomas et al, 2004;Wolf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The only pharmacological treatment used to deal with L-DOPAinduced dyskinesia in PD patients is the noncompetitive antagonist of the N-methyl-D-aspartate (NMDA)-type glutamate receptor, amantadine (Blanpied, Clarke, & Johnson, 2005;Luginger, Wenning, B€ osch, & Poewe, 2000;Meissner et al, 2011;Metman et al, 1999;Ossola et al, 2011;Wandinger et al, 1999). Increased glutamatergic neurotransmission has been associated with the pathophysiology of L-DOPA-induced dyskinesia (Ahmed et al, 2011;Huot, Johnston, Koprich, Fox, & Brotchie, 2013;Morin & Di Paolo, 2014;Papa, Boldry, Engber, Kask, & Chase, 1995;Rylander et al, 2009;Solís, García-Sanz, Herranz, Asensio, & Moratalla, 2016). Nonetheless, pharmacotherapy with amantadine is limited due to the development of central adverse effects including dizziness, confusion, and hallucinations (Macchio, Ito, & Sahgal, 1993;Shannon, Goetz, Carroll, Tanner, & Klawans, 1987;Thomas et al, 2004;Wolf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in rat models, the effects of NMDA antagonists are dependent on whether dyskinesia is due to impairment in the indirect or direct striatal pathway (Flores et al, 2014). An increase in striatal postsynaptic glutamate-5 receptors (mGlu5) has been noted in PD patients and animal models of PD (Morin and Di Paolo, 2014). Mellone et al (2015) reported an abnormal ratio of GluN2A/GluN2B subunit of NMDA receptors in the striatum of postmortem brain specimens from 16 PD patients, 6-OHDA model of PD in male Sprague-Dawley rats, and MPTP monkey model of PD suffering from LID.…”
Section: Neural Substrates Of Lidmentioning
confidence: 99%
“…mGluR5 is a promising therapeutic target and many preclinical models of disease where efficacy has been observed with mGluR5 NAMs include anxiety 15 , GERD 16 , dyskinesias 17 , migraine 18 , fragile X syndrome (FXS) 19 , and Parkinson's disease levodopa induced dyskinesia (PD-LID) 20 . By analyzing the chemical structures of mGluR5 NAMs, all chemotypes can be divided into two types, which depends on whether there is a disubstituted alkyne or not 21 .…”
Section: Introductionmentioning
confidence: 99%